Core-shell structure mediated microstructure and mechanical properties of high entropy alloy CoCrFeNi/Al composites. (October 2021) - Liu, Yunzi; Chen, Jian; Liu, Jiangnan; Zhang, Peng; Wang, Yaqiang
Abstract: In this work, CoCrFeNi high entropy alloy (HEA) with FCC structure as reinforcement has been used to add in the effectiveness of HEA/Al composites, which was fabricated by spark plasma sintering, leading to an in-situ formed shell with FCC + BCC structure surrounding HEA core under higher sintering temperature. This study focuses on two aspects: evaluation of the micromechanics properties through nanoindentation creep tests and analysis of the mechanical properties in composites. Experimental results manifested that the formed shell has higher hardness and nanoindentation creep resistance compared with HEA core, which is attributed to a large number interdiffusion of Al and CoCrFeNi elements along with its small grain size. In comparison with HEA/Al composite without core-shell structure, the compressive strength of HEA/Al composite with core-shell structure is substantially improved about 2.6 times because that the formation hard shells can be regard as reinforcement in composite. However, the cracks are easy to nucleate and rapidly propagate at shell under the applied load, giving rise to ductility decrease in the composite. Highlights: CoCrFeNi/Al composites with and without core shell structure were prepared by SPS. The shell is composed of FCC equiaxed and BCC columnar grains. The shell has lager hardness and higher creep resistance as compared to the core. Yield strength of composite with core shell structure has increased 2.6 times.